The USA and the energy transition of the 21st century: Measures to overcome dependence on China in critical minerals - N. А. Biryukova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2022)
Since the middle of 2010s, international community (developed economies primarily) has been paying increasing attention to the reduction of carbon footprint in the environment by means of large-scale deployment of renewable energy, electrification of transport system and sustainable production of goods. Aspiring to become a global leader of energy transition, the United States of America has already taken a set of measures to stimulate technological growth. Such a challenging task cannot be accomplished without a guaranteed access to the so-called critical minerals. However, the US has encountered growing competition from China in this field. From the beginning of 2000s, China has amassed within its territory a dominant share of global production of critical minerals, acquired access to key foreign extraction centers and thus become virtually a monopolist in the markets. Hence the United States government urgently needs to devise measures to overcome the dependence from China in this regard. The author of the article dwells on the factors which have made the issue of critical minerals (as a recent development of international relations) relevant and politically charged. In its turn, it has led to the securitization of the subject in American official discourse during Trump administration which manifested itself in the ‘mineral security’ concept. The article contains comparative analysis of Trump and Biden administration approaches to navigating the country out of the dependence from China for critical minerals; it also identifies key focus areas of the current US mineral strategy. Respective analysis indicates that Trump administration prioritized bolstering domestic extraction capacity, whereas Biden-Harris administration underscores processing and production segments, mostly due to the pressure from local communities and environmental groups. The author stresses that the Unites States, being unable to contest China’s monopoly as producer and supplier of critical minerals with market instruments, tends to employ human rights discourse to compete with its rival. The ultimate expression of such an approach is Energy Resource Governance Initiative which has been designed to foster high ecological and social standards in global extraction sector. Relying on its partners, the United States intends to use the program to challenge China in commodity markets. The author concludes that despite the effort Washington won’t be able to rid itself of the dependence for Chinese imports in the near future. As for the long-term goals, their achievement is complicated due to both China’s production capacity and experience and insufficient government funding of renewable energy projects in the United States.